Optimizing ODP Device Placement on FTTH Network Using Genetic Algorithms - Pratiwi Hendro Wahyudiono; Ahmad Syafruddin Indrapriyatna; Ismail Yusuf Panessai; Nurus Sabah; Achmad Yani; Abdi Manaf; Nur Iksan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2023)
Currently the problem of Optical Distribution Point (ODP) infrastructure is important in fiber to the home (FTTH) network access because ODP infrastructure development is no longer dependent on demand, so placing ODP manually without a systematic method can cause an increase in the value of optical fiber attenuation. on the length of the cable and cause the cable distribution to be irregular. This study aims to optimize the placement of ODP devices in PT BCV's FTTH network by using the Traveling Salesman Problem (TSP) scheme with the genetic algorithm (GA) approach and using hybrid GA, testing is carried out using Matlab software. Testing with development using Hybrid GA gets the best path with a fitness value of 28.6457 and a computation time of 89.93 seconds.